2021
DOI: 10.3390/nano11092191
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Mussel Inspired Method and “Thiol-Michael” Click Reaction for Biocompatible Alginate-Modified Carbon Nanotubes

Abstract: Carbon nanotubes (CNTs) have attracted great interest in biomedical fields. However, the potential toxicity and poor dispersion of CNTs have greatly limited its application. In this work, a mussel-inspired method combined with the “thiol-Michael” click reaction was used to modify the surface of CNT and improve its properties. Firstly, a CNT was treated with dopamine, and then alginate grafted with L-cysteine was anchored onto the surface of CNT via click reaction, which realized the long-time dispersion of CNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…No significant differences were found between the two nanocarriers. These results are consistent with previous data for CNT, CNT-modified polydopamine, and CNT-modified alginate on MC3T3-E1 and HepG2 cells, demonstrating that the cytocompatibility is concentration-dependent . The obtained results may indicate that cytocompatibility relies on the concentration of CNT used as the drug nanocarrier. , …”
Section: Resultssupporting
confidence: 92%
“…No significant differences were found between the two nanocarriers. These results are consistent with previous data for CNT, CNT-modified polydopamine, and CNT-modified alginate on MC3T3-E1 and HepG2 cells, demonstrating that the cytocompatibility is concentration-dependent . The obtained results may indicate that cytocompatibility relies on the concentration of CNT used as the drug nanocarrier. , …”
Section: Resultssupporting
confidence: 92%
“…Accumulating evidence suggested that the morphology and size of nanomaterials play a critical role in cell behaviors, including adhesion, viability, proliferation, migration, functionalization or differentiation ( Nguyen et al, 2016 ; Zhou et al, 2018 ; Li et al, 2020 ; Liu M. et al, 2021 ; Wang et al, 2021b ; Yang et al, 2021 ; Yao et al, 2021 ). Figure 2A shows that the nanosized HA particles possessed uniform distribution and needle-shaped morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of alginate, measured at ≈ 67 kDa, enabled filter sterilization of the precursors and, therefore, easy to use for 3D cell culture applications. In the scientific literature, several systems have been developed for the formation of alginate hydrogels by covalent cross-linking, including the thiol-ene reaction [32] or the inverse electron-demand Diels-Alder (IEDDA) reaction [33], [34]. However, these reactions have certain drawbacks that limit their use in the biological and medical fields.…”
Section: Discussionmentioning
confidence: 99%